2017
DOI: 10.1017/s0263034617000623
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of extreme ultraviolet emission from laser irradiated targets by surface nanostructures

Abstract: The effects of shape and thickness of a tin surface layer and of the energy of a 170 ps neodymium:yttrium-aluminum-garnet laser pulse on the conversion efficiency (CE) into extreme ultraviolet emission in the 13.5 nm region is investigated. Whereas a CE of up to 1.16% into the 2% reflection band of multilayer Mo/Si optics was measured for a bulk Sn target at a laser energy of 25 mJ, significant CE enhancement up to 1.49% is demonstrated for a 200-nm-thick Sn layer on a microstructured porous alumina substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is shown that mixed, multilayer and surface-structured targets can be used to increase the laser energy absorption. For example, high-Z mixture targets [27], porous or foamlike targets [28][29][30][31], multilayer targets [32,33], nanowire arrays [34][35][36], gratings [37][38][39] and doped aerogel targets [40,41]. In this context, investigations conducted on low density structured materials have shown that foam-attached targets or multilayer targets consisting in a solid substrate coated with a low-density layer offer significant enhancement of laser energy absorption and electron heating leading to higher conversion efficiency of laser energy into x-rays or energetic particles [29-31, 42, 43].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that mixed, multilayer and surface-structured targets can be used to increase the laser energy absorption. For example, high-Z mixture targets [27], porous or foamlike targets [28][29][30][31], multilayer targets [32,33], nanowire arrays [34][35][36], gratings [37][38][39] and doped aerogel targets [40,41]. In this context, investigations conducted on low density structured materials have shown that foam-attached targets or multilayer targets consisting in a solid substrate coated with a low-density layer offer significant enhancement of laser energy absorption and electron heating leading to higher conversion efficiency of laser energy into x-rays or energetic particles [29-31, 42, 43].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of well-defined low density tin targets have a merit for supporting a wide range of materials consisting of various elements, exact shape, pore size, density etc [16][17][18][19][20] . Plasma generated from low density materials or nanostructured targets have a reduced opacity, increasing the CE as the plasma becomes less dense 6,[18][19][20][21][22][23][24][25][26] . Moreover, the flexibility of materials science is exciting for quantum beam sources; the desired wavelength of light can be selected based on specific elements supported by a low density scaffold.…”
mentioning
confidence: 99%